2017
DOI: 10.3389/fnins.2016.00598
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Attenuates Formaldehyde Induced Hyperphosphorylation of Tau Protein and Cytotoxicity in N2a Cells

Abstract: Recent studies have demonstrated that formaldehyde (FA)—induced neurotoxicity is important in the pathogenesis of Alzheimer's disease (AD). Elevated levels of FA have been associated with memory impairments and the main hallmarks of AD pathology, including β-amyloid plaques, tau protein hyperphosphorylation, and neuronal loss. Resveratrol (Res), as a polyphenol anti-oxidant, has been considered to have therapeutic potential for the treatment of AD. However, it has not been elucidated whether Res can exert its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 39 publications
1
41
0
Order By: Relevance
“…To study the influence of the proposed delivery systems on cell culture and analyze possible cytotoxic effects, we used the N2a cell line, a fast-growing mouse neuroblastoma cell line that has been widely used to study neuronal differentiation, neurite growth, synaptogenesis and signaling pathway. Also, N2a cells have been used to study neurotoxicity, Alzheimer's disease and asymmetric division of mammalian cell lines (He et al, 2017;Yang et al, 2014). Cytotoxicity upon treatment with CBZ, D or D-CBZ was measured by colorimetric methods as crystal violet (CV) staining, MTT assay, and neutral red (NR) uptake.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…To study the influence of the proposed delivery systems on cell culture and analyze possible cytotoxic effects, we used the N2a cell line, a fast-growing mouse neuroblastoma cell line that has been widely used to study neuronal differentiation, neurite growth, synaptogenesis and signaling pathway. Also, N2a cells have been used to study neurotoxicity, Alzheimer's disease and asymmetric division of mammalian cell lines (He et al, 2017;Yang et al, 2014). Cytotoxicity upon treatment with CBZ, D or D-CBZ was measured by colorimetric methods as crystal violet (CV) staining, MTT assay, and neutral red (NR) uptake.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…Recently, resveratrol has gained more interest to treat AD due to its greater neuroprotective effect, and many studies confirmed that resveratrol treatment significantly improved the cognition and biochemical parameters. [114][115][116][117][118][119][120][121][122][123] Recently, resveratrol-loaded SLN was studied for its bioavailability and brain delivery. Resveratrol was efficiently delivered to the brain and exhibited its potential bioactivity.…”
Section: Anti-alzheimer's Effectmentioning
confidence: 99%
“…In support, a correlation with cognitive dysfunction in MCI and AD subjects was found with the reduction of T286‐autophosphorylation in apical dendrites of granule cells of the DG . Resveratrol was shown to decrease τ hyperphosphorylation via suppression of GSK3β and CaMKII activities in N2A cells exposed to formaldehyde . Strong and sustained stress‐like acute severe CO poisoning could lead to both calpain and CaMKII expression and activation .…”
Section: Calpain In Alzheimer’s Diseasementioning
confidence: 73%